Management of resources in nursing: beyond leadership. Our will to be and do - Delby Antonio Cano Serna; Natalia Andrea Correa Bolívar; Weimar Alexander Flórez Rendón; Yaison Dorney Giraldo Giraldo; Mónica Katerín Monsalve Cuervo; Andrés Felipe Restrepo Otálvaro (Universidad de Antioquia, 2013)
This article reflects upon the reach of the contribution from nursing in the management and development of public policies for adequate assignment of resources that facilitate better healthcare in the Colombian population.